The Effect of Shore Leave Crew on Watch Duty on Passenger Ships - Musriady; Ismail; Danduru, Arifuddin; Irwansyah; Noegraha, Andi Dirga (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2026)
The shipping industry plays a vital role in supporting passenger mobility and goods distribution in Indonesia. However, one of the challenges faced is the management of crew working hours and rest periods, particularly in relation to shore leave activities. This study aims to analyze the effect of crew shore leave on the effectiveness of watchkeeping duties on passenger ships and the impact of crew shore leave on the readiness and performance of watchkeeping crews. The research method used is a quantitative approach with an instrument in the form of a questionnaire distributed to 35 passenger ship crew members on duty at PT Pelni Makassar. The data were analyzed using descriptive statistics, regression tests, and ANOVA. The results of the study indicate that shore leave crew has a significant effect on the quality of watchkeeping, particularly in terms of physical readiness, mental readiness, and reduction of fatigue risk. These findings emphasize the importance of good shore leave schedule management to support shipping safety.